Oscillating, relaxating, and translating mobility of Li+ ions in the LiNbGeO5 monocrystal - S. Y. Stefanovich; V. V. Fomitchyov; V. V. Konovalova; A. V. Mosunov; B. V. Mill (Тонкие химические технологии)
Dielectric properties of single crystals of LiNbGeO5, crystallizing in the andalusite (β-Al2SiO5) structure, have been studied. Dielectric and conducting properties along the major crystallographic axes were investigated at frequencies from 1 to 1000 kHz and in the range of temperatures between 100 and 600 K. Determined potential barriers between the equilibrium positions of Li+ ions are classified as low energy (0.23-0.79 eV, along the a axis) and high energy (0.9-1.90 eV, along the a, b, and c axes). Additional interstitial sites with the distances between them 0.3-0.4 Å have been found along the a axis, while no such sites observed along the b and c axes. Activation energy (Ea) in the direction a is 0.47 eV and ?a(570 K) = 2.10-5 S/cm, which correspond to the super-ionic conductivity.